(untitled) (Annual of the Faculty of Philosophy in Skopje, 2016)
The article discusses some key concepts and problems in contemporary philosophy mind and cognitive science: concept of naturalism, intertheoretic reduction, functionalism and supervenience. An overview is given on reception and future of the philosophy of mind in Macedonia.